Patterns of Community Empowerment Through Family Welfare Programs - Pratama, Tegu Chaniago; Fadri, Zainal; Spencher, Jaesik (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This research is to make a pattern of Community Empowerment Through the Family Welfare Program in Nagari Tabek, Tanah Datar Regency. So that this study aims to describe the pattern of the Family Welfare Program in Nagari Tabek, Tanah Datar Regency. The type of researcher that the writer did was qualitative research with descriptive method. The research subjects were the head of the PKK in Nagari Tabek, Mr. Wali Nagari and members of the PKK. Data collection techniques used are interviews, observation and documentation. The analysis procedure uses data reduction steps, data presentation and conclusion drawing. The data assurance technique uses triangulation. The results of this study can be concluded that the PKK program in Nagari Tabek has been tried for actualization but it is still not effective because it is still constrained by several factors such as budgetary funds, time effectiveness, miscommunication of the community in cooperation so that the knowledge of some elements or members of the main function of the program is minimal. PKK.